2013
DOI: 10.1155/2013/652604
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-Visible and Fluorescence Spectroscopy Techniques Are Important Diagnostic Tools during the Progression of Atherosclerosis: Diet Zinc Supplementation Retarded or Delayed Atherosclerosis

Abstract: Background. In this study, we examined whether UV-visible and fluorescence spectroscopy techniques detect the progression of atherosclerosis in serum of rabbits fed on high-cholesterol diet (HCD) and HCD supplemented with zinc (HCD + Zn) compared with the control. Methods. The control rabbits group was fed on 100 g/day of normal diet. The HCD group was fed on Purina Certified Rabbit Chow supplemented with 1.0% cholesterol plus 1.0% olive oil (100 g/day) for the same period. The HCD + Zn group was fed on normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In atherogenic mouse models, zinc supplementation suppressed the abnormal plasma lipid profile and the proinflammatory events in atherosclerosis [ 190 ]. Studies also found that dietary zinc supplementation significantly reduced total cholesterol accumulation in the aorta and inhibit the development of aortic atherogenesis in HFD-fed New Zealand rabbits [ 193 , 194 , 195 , 196 ]. A recent study conducted by Cheng et al [ 197 ] suggests the role of zinc influx in monocyte adhesion and recruitment.…”
Section: Zinc and Atherosclerosis: Animal And Human Studiesmentioning
confidence: 99%
“…In atherogenic mouse models, zinc supplementation suppressed the abnormal plasma lipid profile and the proinflammatory events in atherosclerosis [ 190 ]. Studies also found that dietary zinc supplementation significantly reduced total cholesterol accumulation in the aorta and inhibit the development of aortic atherogenesis in HFD-fed New Zealand rabbits [ 193 , 194 , 195 , 196 ]. A recent study conducted by Cheng et al [ 197 ] suggests the role of zinc influx in monocyte adhesion and recruitment.…”
Section: Zinc and Atherosclerosis: Animal And Human Studiesmentioning
confidence: 99%
“…Despite these data, the amount of dietary cholesterol, the diet formula, and the duration of cholesterol feeding necessary to induce translated atherosclerosis are not conclusive among experimental studies (e.g., see [7,8]). In this line, Prof. Watanabe and colleagues [9] partially solved this problem by producing a genetic rabbit model of hypercholesterolemia many years ago.…”
Section: Introductionmentioning
confidence: 99%